International organisations, non-state actors, and the formation of customary international law - Droubi, Sufyan; D'Aspremont, Jean (Manchester : Manchester University Press, 2021)
This collection of essays provides the most comprehensive study of the theory and practice of the contribution of international organisations and non-state actors to the formation of customary international law. The book offers new practical and theoretical perspectives on one of the most complex questions about the making of international law.
Previously issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 12, 2021).
Keywords: Customary law, International -- Interpretation and construction; International agencies; Non-governmental organizations; Law; International law